Solving Nonlinear Second Order Delay Eigenvalue Problems by Least Square Method - Israa M. Salman; Eman A. Abdul-Razzaq (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2020)
The aim of this paper is to study the nonlinear delay second order eigenvalue problems which consists of delay ordinary differential equations, in fact one of the expansion methods that is called the least square method which will be developed to solve this kind of problems.